TIME-TO-OPTIMAL CONTROL OF HYPERTENSION USING KAPLAN-MEIER ESTIMATOR, COX PROPORTIONAL HAZARD AND WEIBULL MODEL - Usman, Umar; Arkilla, Bello Magaji; Ismail, Abduljalil Alfa; Dauda, Usman (FUDMA Journal of Sciences, 2022)
Hypertension is a worldwide public health challenge. The study investigated the time it takes to attain an optimal control of hypertension and the major factors that influence the control in Specialist Hospital, Sokoto.A retrospective cohort study was conducted involving 300 patient records. The population consisted all hypertensive patients on follow-ups at Specialist Hospital Sokoto from1st February, 2015 to 1st February, 2021.Statistical Package for the Social Sciences version 20 and R software were used for descriptive, Kaplan-Meier estimator, Cox Proportional Regression (CPH) Model and Weibull Regression Model analyses.Hypertensive patients attain an optimal control after a median survival time of 40.43 (at 95% CI: 33.67- 47.19) months (3.37 years) and mean survival time of 44.18 (CI: 37.24-51.12) months (3.68 years). The CPH analysis revealed that the factors that influenced an optimal control of hypertension were body mass index (BMI) (P
Keywords: Hypertension, Time-to-Event, Optimal control, Cox proportional hazard, Weibull model